Assessment of: self-management skills towards transition readiness and patient portal use among Hispanic adolescent and young adult patients. Issue 1 (26th April 2020) - Allende-Richter, Sophie; Ramirez, Melanie; Khoury, Zana; Bourgeois, Fabienne; Epee-Bounya, Alexandra; O'Hare, Kitty
Abstract : We conducted a 15-item self-answered survey to assess self-management skills and explore interest in a patient portal among publicly insured Hispanic youths ages 12–25. Out of 61 participants, 33% did not know how to schedule an appointment, 50% how to refill prescriptions, 58% how to access their personal health information, 84% were unaware of the portal and 92% never used it. Referring to the portal as an online application increased participants interest by 39%. Although study participants exhibit low self-management skills and awareness of a patient portal, most welcome using it to manage their health. Further research is needed to validate whether a patient portal can promote self-management skills towards transition readiness among Hispanic youths.